MODELING THE HARDENING OF CARBON STEELS AFTER QUENCHING AND TEMPERING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the paper, after an overview and defined tasks, a methodology is applied and a model is derived for establishing the dependence of hardness on carbon content, hardness after hardening and tempering temperature after hardening for the entire range of carbon steels from structural to tool steels. The research was based on eight steels and four tempering temperatures formed in a total of 32 combinations. First, one-dimensional dependences of hardness change on carbon content were derived for each annealing temperature, then accuracy was improved with a three-control parameter model. The derived model was examined and its theoretical maximum was corrected. The difference between the theoretical and the real logical maxima amounts to 17.44%. For all specified extremes, the heat treatment modes are defined.